Targeted professional development strategies to increase teachers’ efficacy for educating students with special needs - Yavuz, Olcay (Çağdaş Yönetim Bilimleri Dergisi, 2020)
There is a significant increase in the number of students with disabilities. However, many general education teachers report that they feel ill-equipped to educate a classroom of students with diverse special education and learning needs. In this qualitative study, the structured focus group interviews were conducted to determine the PD opportunities and characteristics that general education teachers perceive to influence their sense of self-efficacy for educating students with special needs. The results of the focus group discussions revealed that there are several targeted professional development strategies to increase teachers’ efficacy for educating students with special needs. This study makes recommendations for the research supported professional development activities, focused on educating students with special needs, provided to general education teachers.
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found